The distribution of selected metals in the surface sediment of Langkawi Coast, Malaysia - Md Suhaimi, Mohd Zahir; John, Akbar; Yunus, Kamaruzzaman; Khan Chowdhury, Ahmed Jalal; Saad, Shahbudin; Miskon, Mohd Fuad; Faudzi, Fikriah; Sa'ari, Anies Aznida (Oriental Scientific Publishing Co., 2012)
Surface sediment samples were collected from five stations covering 25 sampling points from the Langkawi coastal waters. Concentration of metals such as Zn, Cu, Pb, Cd, and Cr were determined using an Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The detected concentration range of Zn, Cu, Pb, Cd, and Cr were 41.02-137.1 μgg-1, 14.36-46.32 μg.g-1, 14.4- 38.6 μg.g-1, 0.6-2.4 μg.g-1, and 40.5-84.5 μg.g-1 dry weight respectively. Enrichment factors (EF) analysis showed that the source of Zn, Cu and Cr in the sampling areas were predominantly of terrigenous in origin while the source of Pb and Cd were slightly of anthropogenic in nature.